Use of CBD for treatment of anxiety and depression - Simões , Deise Vimaana Santos de Souza; Freitas , João Fábio de; Martins , Hyan Coelho (Seven Editora, 2024)
This literature review article explores the use of cannabidiol (CBD) in the treatment of anxiety and depression. It analyzes CBD’s mechanisms of action, clinical evidence, efficacy, safety, and regulation. Anxiety and depression are common disorders, and CBD has been highlighted as a possible therapy. CBD acts on the endocannabinoid system and the serotonergic system. Clinical studies show reduced social anxiety and antidepressant effects. However, research is still preliminary, and effectiveness may vary. CBD has a favorable safety profile but can cause mild side effects. Regulation varies between countries, so it is essential to be aware of local laws. DOI:https://doi.org/10.56238/sevened2024.007-084